Translation shifts in aljazeera and BBC translations of obama’s speech on the Arab spring - Tawfiq, Nazar Mohammed (2019)
Media translation is among the subfields of translation studies that has grown in the last two decades, especially the translation of political discourse. However, there are scarce studies on tendencies or policies of international media agencies in terms of translator’s behaviour and the nature of the translated texts. The current study seeks to analyse and contrast the Arabic translations of Obama’s speech on Arab Spring delivered at the Department of State in 2011 which was translated by Aljazeera and BBC Arabic satellite television channels. For this purpose, four translation models; Molina and Albir (2002), Schjoldager (2008), Dukāte (2009) and Darwish (2010) were employed to detect and analyse translation shifts exercised by these two channels. The qualitative content analysis was adopted, where each translation was contrasted to the original English text so that translation shifts can be identified. The coding of the translations of Aljazeera and BBC was performed through a special application added to the Microsoft Office Word 2016. The study found that translation shifts were a priority for both media channels.